ChemInform Abstract: Polymers for Electronics and Spintronics. Issue 5 (4th February 2014) - Bujak, Piotr; Kulszewicz‐Bajer, Irena; Zagorska, Malgorzata; Maurel, Vincent; Wielgus, Ireneusz; Pron, Adam
Abstract Review: <550 refs.